NUSYUZ DAN SOLUSINYA DALAM ISLAM - Fitri, Abd. Basit Misbachul; Hi’mah, Ika Izzatil (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
Nusyuz can occur in married life. Both parties, the husband and the wife, can engage in nusyuz by neglecting the duties that they should fulfill properly. This article discusses the definition of nusyuz, the classification of nusyuz, factors causing nusyuz, and solutions if nusyuz occurs. Although both spouses can engage in nusyuz, there are differences in the solutions for nusyuz by the wife and the solutions for nusyuz by the husband. Nusyuz actions need to be anticipated so that married life can be sakinah, mawaddah wa rahmah, with each spouse fulfilling their duties properly.